University Studets’ Experience Of Pre-Service Studen-Teacher Teaching English Aboard: An Interview Study of A Student Exchange Program - Anisa Candra Rukmana; Angga Taufan Dayu; Raudatul Haura (Borneo Educational Journal (Borju), 2021)
Educational institutions carry out several programs that are able to support the development of their students in preparation for becoming a teacher. Pre-service student teaching aboard is one of executable program. Through this international teaching, pre-service teachers got more dynamic experiences. Not to mention, the status of English in the country where they work is a second language. This research show the result regarding the challenges faced by student exchange participants while participating in pre-service teacher programs abroad and the impact of the experience they gained on their self-efficacy as future teacher candidates. there are so many challenges they have to face; starting from participating in the training provided by the faculty where they will be trained in their English language skills and monitored for their behavior for several days; find out about the school system and curriculum taught in the Philippines and then study it; looking for references on socio-cultural life to find out what can and cannot be done; adapting to the new school and living environment; language gap that makes their communication less fluent; different English terms; culture shock such as the striking attitude of some local people, speaking style; the weather is different from the country of origin. As well as the improvements they experienced after doing this program such as their confidence in their self-efficacy as teachers in the future.